Longitudinal assessment of the health-related quality of life of children and adolescents with chronic kidney disease - Guha, C; van Zwieten, A; Khalid, R; Kim, S; Walker, A; Francis, A; Didsbury, M; Teixeira-Pinto, A; Barton, B; Prestidge, C; Lancsar, E; Mackie, F; et al. (Elsevier, 2022)
In this multi-center longitudinal cohort study conducted in Australia and New Zealand, we assessed the trajectories of health-related quality of life (HRQoL) in children with chronic kidney disease (CKD) over time. A total of 377 children (aged 6-18 years) with CKD stages 1-5 (pre-dialysis), dialysis, or transplant, were followed biennially for four years. Multi Attribute Utility (MAU) scores of HRQoL were measured at baseline and at two and four years using the McMaster Health Utilities Index Mark 3 tool, a generic multi-attribute, preference-based system. A multivariable linear mixed model was used to assess the trajectories of HRQoL over time in 199 children with CKD stage 1-5, 43 children receiving dialysis and 135 kidney transplant recipients. An interaction between CKD stage at baseline and follow-up time indicated that the slopes of the HRQoL scores differed between children by CKD stage at inception. Over half of the cohort on dialysis at baseline had received a kidney transplant by the end of year four and the MAU scores of these children increased by a meaningful amount averaging 0.05 (95% confidence interval 0.01 to 0.09) per year in comparison to those who were transplant recipients at baseline. The mean difference between baseline and year two MAU scores was 0.09 (95% confidence interval -0.05, 0.23), (Cohen’s d effect size 0.31). Thus, improvement in HRQoL over time of children on dialysis at baseline was likely to have been driven by their transition from dialysis to transplantation. Additionally, children with CKD stage 1-5 and transplant recipients at baseline had no changes in their disease stage or treatment modality and experienced stable HRQoL over time.